2018
DOI: 10.1016/j.molcel.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine-1 of RNA Polymerase II CTD Controls Global Termination of Gene Transcription in Mammals

Abstract: The carboxy-terminal domain (CTD) of RNA polymerase (Pol) II is composed of a repetition of YSPTSPS heptads and functions as a loading platform for protein complexes that regulate transcription, splicing, and maturation of RNAs. Here, we studied mammalian CTD mutants to analyze the function of tyrosine1 residues in the transcription cycle. Mutation of 3/4 of the tyrosine residues (YFFF mutant) resulted in a massive read-through transcription phenotype in the antisense direction of promoters as well as in the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
73
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 64 publications
9
73
0
Order By: Relevance
“…We focused on a set of Integrator-dependent genes and found that Integrator catalyzes premature transcription termination of these genes (Figs. 6, 7), which is consistent with prior studies that suggested roles for Integrator in termination (Skaar et al 2015;Shah et al 2018;Gómez-Orte et al 2019). Some of these genes (CG8620, Pepck1, and Sirup) have promoterproximal RNAPII that rapidly turns over (Shao and Zeitlinger 2017), which may indicate that Integrator can aid in clearing paused or stalled RNAPII.…”
Section: Discussionsupporting
confidence: 87%
“…We focused on a set of Integrator-dependent genes and found that Integrator catalyzes premature transcription termination of these genes (Figs. 6, 7), which is consistent with prior studies that suggested roles for Integrator in termination (Skaar et al 2015;Shah et al 2018;Gómez-Orte et al 2019). Some of these genes (CG8620, Pepck1, and Sirup) have promoterproximal RNAPII that rapidly turns over (Shao and Zeitlinger 2017), which may indicate that Integrator can aid in clearing paused or stalled RNAPII.…”
Section: Discussionsupporting
confidence: 87%
“…The role of PNUTS is thought to reflect the essential nature of PNUTS/PP1 since differential phosphorylation of the CTD of Pol II has been proposed to regulate the directionality of transcription at bi-directional promoters. Specifically, Tyr1 and Ser1 hyperphosphorylation of Pol II have been shown to be associated with antisense divergent transcription at mammalian promoters [112][113][114]. Spt5 regulation of Pol II elongation is involved in control of divergent antisense transcription as well as readthrough transcription at 3' end of genes in yeast [2,115], representing an additional target of PNUTS/PP1 regulation of transcription at both ends of genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the puzzling requirement for multiple repeats in the CTD has yet to be explained. Extensive evidence supports for a requirement of tyrosine or serine phosphorylation and dephosphorylation of the CTD during transcription cycle (5)(6)(7)(8)(9)(10)(11)(12). In addition, genetic studies in budding yeast demonstrate that pairs of heptad CTD repeats constitute the essential functional unit (13,14).…”
Section: Introductionmentioning
confidence: 98%